Centrifuge modelling of rainfall-induced landslides in unsaturated soil slopes - Matziaris, Vasileios (2019)
Landslides and debris flows are geohazards common to countries with mountainous terrains. A significant number of rainfall-induced landslides occurs in regions with tropical and subtropical climates where residual and colluvial soils are widespread. This study is in the context of the Innovative Training Network project MUMOLADE (Multiscale Modelling of Landslides and Debris Flows) which aims to study the multi-scale and multi-phase analysis of landslides and debris flows. The research presented here aims to investigate the initiation conditions of landslides in soil slopes under varied rainfall conditions.